Naegleria fowleri: Portrait of a Cerebral Killer - Nguyen The Nguyen Phung; Huong Thien Pham; Thuc Thanh Tran; Vu Hoang Dinh; Nhut Minh Tran; Nuong Ai Nguyen Tran; Minh Quang Ngoc Ngo; Huong Thanh Thi Nguyen; Duy Khanh Tran; Thao Kieu Thi Le; Camelia Quek; Van Hung Pham; et al. (Diagnostics)
Background: Primary amebic meningoencephalitis (PAM) caused by Naegleria fowleri is a rare and devastating infection of the central nervous system, often diagnosed late, due to its rapid progression and nonspecific symptoms. Case Presentation: We report one of the youngest documented pediatric Vietnamese cases of PAM in a 10-month-old girl from the Mekong Delta, Vietnam. The diagnosis was confirmed through multiplex real-time PCR (MPL-rPCR), microscopy, and sequencing. Clinical data were gathered retrospectively from medical records, and additional details were provided by the patient’s family. Treatment regimens, disease progression, and diagnostic challenges were reviewed and compared to existing literature. With intensive treatment, the child survived for 14 days, representing one of the longest reported pediatric PAM survival durations. No direct exposure to untreated freshwater or other typical risk factors for Naegleria fowleri infection was identified, underscoring the unique epidemiological nature of this case. MPL-rPCR enabled timely detection of the pathogen and demonstrated its utility in resource-limited settings. Conclusions: This case highlights the critical need for rapid, accessible diagnostic tools such as MPL-rPCR, particularly in resource-constrained environments where traditional diagnostics may not be feasible. It also emphasizes the importance of international collaboration and investment in cost-effective diagnostics and novel therapeutic strategies. The geographical expansion of PAM due to climate change further underscores the urgency of these measures to improve health outcomes in vulnerable populations.